School in the border municipalities of Eastern Serbia - Trifunović Vesna S.; Živković Predrag Ž. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2016)
Border municipalities in eastern Serbia have peripheral position in relation to the central state territory: geographical distance from the administrative, political, economic and cultural center shaping their overall social development, which is generally far behind the development of other parts of Serbia. At various stages of transition, starting from the nineties to the present, the border municipalities were, it seems, more exposed to the negative effects of the neoliberal development strategy: there was a change of ownership of industry, as well as a deindustrialization, which led to significant reduction of the workforce. The devastation of the economies in these areas has intensified negative demographic processes in the border municipalities of Eastern Serbia with the onset of the economic crisis in the eighties and the subsequent processes there caused: (a) depopulation (population between census periods from 1991 to 2011 fell by more than 20% of the territory of Bor district), (b) reduction in the birth rate, which for decades was showing negative trends (eg. natural growth rate in the Negotin krajina, according to the Census of 2011, amounts to -6.7 % annually) (v) migration of the young, working population (Census 2011) shows that nearly one-quarter of the economically active population of the Bor district 'work abroad', ie. employment is found in western European countries, they educate their own children there and, apparently, do not intend to return to the place of birth. The devastation of the economy leads to a legitimate social devastation and collapse of culture (Mitrović, 2009) and education. The main parameter to be monitored in the new neoliberal strategies of development is economic growth, which points to the direction of changes in macroeconomic processes, but not to the improvement of the quality of life of people who participate in these processes. The achieved rate of economic growth does not automatically provide sustainable development of all areas of society, especially not their balanced development. Therefore, different development policies, such as education (and / or educational) policy, in addition to economic parameters must take into account other parameters relevant to the allocation of decision-making. The question of the network of schools, we believe, is not primarily a question of the commercial viability of their establishment and maintenance, but the crucial question of survival of the impoverished and emptied border municipalities. According to data from the School Administration of Zaječar, during the school year 2011/12, shows that (a) complete (eight-year schools) do not exist in all observed municipalities, which raises the issue of equal opportunities of education (access to resources - time and financial) and (b) offered educational profiles of secondary schools were reduced compared to the educational profiles of the larger and more developed municipal centers in Serbia, which leads to inequality of high school students in the choice of a profession: the same were referred for decision-making in the framework of the existing modest offer and not in accordance with their own interests and predispositions. The authors believe that the basic guidelines for future educational policy must not be guided solely by profitability and efficiency to maintain the existing school network and to reduce it in the border municipalities, but by interests that will enable the realization of the principle of justice in education and dispersed school networks in the Borderlands, thus providing an opportunity for its sustainable development.